Anaerobic and Aerobic Treatment of Chicken Manure: Biogas and Compost Production, Kinetic Study and Flies Alleviation Test - KOK, CLARICE HUI YI (2021)
Anaerobic digestion (AD) and aerobic composting (AC) are typical unit operations for poultry manure treatment. In this study, AD of chicken manure (CM) and sawdust (SD) were conducted under mesophilic temperature (35°C), with different mixing ratio in order to achieve carbon-nitrogen ratio (C/N) 20, 25, 30 and 35. Reactor CM produced the highest biogas yield at 239.39 ml/g VS. However, the highest methane yield corresponds to reactor C/N 35, generated 53.73 ml/g VS of methane, 378% higher than reactor CM. Thus, optimum C/N ratio for co-digestion of CM and SD is C/N 35. Modified Gompertz (MG) model and Cone model have shown good fit to the methane data, with high R2 ranged between 0.955-1.0 and low root-mean-square deviation (RMSD) with the range 0.002-0.417. Aerobic composting (AC) process of digestate was divided into two piles, one associated with effective microorganisms (EM) whereas the other was only watered with tap water. At the end of AC, most composts, except compost CM, did not reduced to C/N 20, a widely accepted compost maturation C/N indicator. Carbon (C) content of composts between compost with EM and without EM did not show significant difference, whereas nitrogen (N) content of compost without EM were generally higher than compost with EM. The result implied that EM was not effective on improving rate of decomposition of digestate. However, EM is useful in improving the mineralization of phosphorus (P) and potassium (K) in compost. All composts with EM had higher nutrient content (P and K) compared with non-EM assisted compost. From fly test analysis, the attraction of flies to CM were eliminated after manure treatment of AD and AC where no fly was recorded in the trap as compared to raw manure. Research work in AD and AC have so far are remained separated despite their potential for system integration for full treatment process and producing value-added products. The integration of these processes can solve the environmental problems associated with improper manure disposal and presents an avenue for value creations.